2022
DOI: 10.1093/ajcn/nqac086
|View full text |Cite
|
Sign up to set email alerts
|

Sources of dietary gluten in the first 2 years of life and associations with celiac disease autoimmunity and celiac disease in Swedish genetically predisposed children: The Environmental Determinants of Diabetes in the Young (TEDDY) study

Abstract: Background High gluten intake is associated with increased risk of celiac disease (CD) in children at genetic risk. Objectives To investigate if different dietary gluten sources up to age two years confer different risks of celiac disease autoimmunity (CDA) and CD in children at genetic risk. Design Three-day food records were collected at age six, nine, 12, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 41 publications
1
14
0
2
Order By: Relevance
“…Our study is in line with previous prospective cohorts of children at risk of CD (10,11) showing different clinical outcomes over time. Within our cohort, the rise of aDGPs IgG has displayed a similar pattern both in CD and in the larger CD spectrum cohort, with AUCs almost overlapping.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study is in line with previous prospective cohorts of children at risk of CD (10,11) showing different clinical outcomes over time. Within our cohort, the rise of aDGPs IgG has displayed a similar pattern both in CD and in the larger CD spectrum cohort, with AUCs almost overlapping.…”
Section: Discussionsupporting
confidence: 92%
“…Granda Ospedale Maggiore Policlinico, University of Milan, Milan, Italy;7 Pediatric Unit "Bruno Trambusti," Osp Pediatrico Giovanni XXIII, University of Bari, Bari, Italy; 8 Celiac Disease Referral Center, "San Giovanni di Dio e Ruggi d'Aragona" University Hospital, Pole of Cava de' Tirreni, Salerno, Italy;9 Pediatric Hepatology Gastroenterology and Transplant Unit, Ospedale Papa Giovanni XXIII Bergamo, Bergamo, Italy;10 Pediatrics, IRCCS Ospedale Giannina Gaslini, Genova, Italy;11 Pediatrics, Univ. Politec.…”
mentioning
confidence: 99%
“…Eight prospective cohort studies (PreventCD, TEDDY, DAISY, Generation R, BABYDIAB, DIABIMMUNE, MoBA and ABIS) reported in 15 publications were included 11–15,29–38 . Eight new publications of five cohort studies (PreventCD, TEDDY, DAISY, DIABIMMUNE and MoBA) were identified 11–15,29,37,38 . The PreventCD cohort includes children who continued follow‐up for the PreventCD randomised controlled trial 12,15 .…”
Section: Resultsmentioning
confidence: 99%
“…Es conocido el paradigma del posible rol viral como factor desencadenante de la autoinmunidad en la DBT1. Muchos grupos a nivel mundial estudiaron el impacto de la pandemia en los debuts de DBT1 y postularon diferentes hipótesis para explicar lo sucedido 7 . Un estudio retrospectivo publicado en Finlandia durante el 2021 analizó el ingreso a terapia intensiva de pacientes con diagnóstico de debut diabético durante 2020 y el posible rol del SARS-CoV-2 en la génesis de la patología; halló que la incidencia de pacientes que ingresaron a unidad de cuidados intensivos había aumentado de 2.89/100.000 personas por año durante el período 2016-2019 a 9.35/100.000 personas por año en el año 2020 (95%) (p<0.001).…”
Section: Discussionunclassified
“…Al igual que al resto de los autores, nos resulta difícil dilucidar la causa exacta de dicho incremento. Similar a un estudio publicado en España, múltiples factores medioambientales podrían estar involucrados: el aislamiento domiciliario, el sedentarismo que conllevó, la distorsión horaria con pérdida de ritmos sueño-vigilia, modificaciones en la dieta, estrés, consultas tardías a los centros de salud, entre otras, podrían ser algunas de las posibles causantes de dicho incremento durante la pandemia 7 . Según el estudio de factores medioambientales de diabetes en pacientes jóvenes (TEDDY), publicado en el año 2018, la DBT1 es una patología de origen multifactorial, en la que pueden estar implicados factores genéticos, infecciosos (vacunas, virus, microbioma), dietarios, físicos, psicológicos y autoinmunes, como lo es su asociación con enfermedades como la celiaquía y de la tiroides.…”
Section: Discussionunclassified